What Should Churches Post on Facebook? An Exploratory Study of the Perceived Contribution of Facebook Posts to the Mission of Churches - Dunaetz, David R. ca. 21. Jh.; Heath, Chelsea; Recto, Raisa; Soria, Danny; Wilden, Stephanie J. (2023)
Facebook is the most popular social networking site in the world and is used by many churches. This study seeks to discover the type of Facebook posts that most contribute to the perceived spiritual formation of church attenders as defined by typical church mission statements. A broad range of church attenders who use Facebook (N = 161) completed an online survey focusing on their church's Facebook page. They indicated the degree to which they believe various types of their church's Facebook posts contributed to their spiritual formation, specifically, their relationship with God, their relationship with fellow believers, their personal spiritual growth, and their involvement in ministry or service. They also indicated what type of posts they would like to see more frequently from their church. An exploratory analysis found that posts that had greater cognitive content (specifically, live broadcasts, video recordings, announcements, and devotionals) were perceived to contribute more to church attenders’ spiritual formation than did posts with less cognitive content (humorous memes, photos, inspirational quotations, and external links). Confirming these results, participants also expressed a preference for their church to make more posts with high cognitive content than posts with low cognitive content. These results lead to several applications of how churches can better use Facebook to contribute to their mission.
Keywords: Social Media; Quantitative Study; Spiritual Formation; Mission; Church; Facebook